The Effect of Practical Application of Virtual Reality Technology on High School Science Teachers' Perceptions of Its Use in the Educational Process (Damascus University Journal of educational and Psychologyical sciences, 2026)
Virtual reality is one of the modern technologies that has revolutionized many fields of life, including the educational sector. Therefore, this study aimed to explore the practical impact of virtual reality experiences on the perceptions of high school science teachers in Kuwait regarding the use of virtual reality in education. The study sample consisted of 43 science teachers divided into a control group of 19 teachers and an experimental group of 24. The study followed a quasi-experimental design appropriate for the nature and objectives of the research. A 13-item questionnaire was developed to measure the teachers' perceptions of using virtual reality in science education. Both the experimental and control groups completed a pre-questionnaire, read an article focused on using virtual reality, and then completed a post-questionnaire. However, after reading the article, the experimental group attended a hands-on training workshop on using virtual reality technology in teaching various high school science subjects. The results showed no statistically significant differences between the two groups in the pre-questionnaire results, indicating that they were equivalent in their perceptions of using virtual reality in science teaching. However, the post-questionnaire results revealed statistically significant differences in favor of the experimental group. Finally, when comparing each group's pre- and post-questionnaire results separately, statistically significant differences were found only in the experimental group. This indicates that the practical application of virtual reality technology positively influences the perceptions and beliefs of high school science teachers.
Keywords: Virtual Reality; Educational Technology; Science Teaching; Science Subjects; Technological Innovations